Chronic ulcerative stomatitis: Case series of an under‐recognized entity. (25th September 2018) - Ko, Eugene M.; Danciu, Theodora E.; Fullen, Douglas R.; Chan, May P.
Abstract : Chronic ulcerative stomatitis (CUS) is a mucocutaneous condition characterized by chronic relapsing and remitting oral ulcers and erosions. This condition remains under‐recognized among dermatopathologists, possibly because of common misdiagnosis as oral erosive lichen planus (LP). We report five cases of CUS in order to raise awareness of this uncommon condition. All patients presented with desquamative gingivitis and/or oral erosions, with biopsies showing lichenoid mucositis and epithelial nuclear IgG deposition on direct immunofluorescence. Recognition of the characteristic direct immunofluorescence findings allows for distinction of chronic ulcerative stomatitis from oral LP and appropriate therapy.